Criticism, practice, pedagogy: creative convergence through A.S. Byatt’s Babel Tower - Helen E. MUNDLER (E-REA)
This article examines how literary criticism and the teaching of creative writing can be brought together. Specifically, it analyses an aspect of intradiegetic literary creation in A.S. Byatt’s Babel Tower, the third novel of the Frederica Quartet, in which Frederic Potter, a teacher of English literature and would-be novelist, is afflicted by writer’s block. Frederica works through this problem by returning to a project begun in The Virgin in the Garden, the first novel of the tetralogy, entitled Laminations. The idea of this intradiegetic text is to write in a series of apparently separate layers, hence the title, and then to allow these layers to come together to create new meaning. In Babel Tower, she experiments with cut-up texts, in the style of William Burroughs.This article outlines a creative writing teaching technique intended to trigger ideas which build on Frederica’s cut-ups, transposing her attempt to find new signifiers, and thus express new ideas, to the realm of the altered book (also known as black-out or erasure). It suggests a technique for distilling Byatt’s long and complex commentary on creativity – a life’s work – into a creative writing teaching method which could be used with students in French universities.